Natural Object Learning Improves Early Numeracy and Number Symbol Recognition in Preschoolers: Pembelajaran dengan Objek Alami Meningkatkan Kemampuan Berhitung Awal dan Pengenalan Simbol Angka pada Anak Prasekolah - Umi Soifah; Choirun Nisak Aulina (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Early childhood is a critical period for cognitive development, including foundational numeracy skills such as recognizing number symbols. Specific Background Children aged 4–5 years at TK Islam Al-Faqih showed difficulties identifying number symbols 1–10 due to learning activities that relied on abstract and less engaging media. Knowledge Gap There was a need for contextual and concrete learning media that align with children’s developmental characteristics to address low initial performance in number symbol recognition. Aims This study evaluated the use of natural objects as learning media to support number symbol recognition among children aged 4–5 years through a Classroom Action Research design. Results Findings across two action cycles demonstrated progressive improvement in children’s abilities to mention number symbols, count using natural objects, and match quantities with symbols, with learning mastery increasing from 0% in the pre-cycle to 67% in Cycle I and 80% in Cycle II. Novelty The study demonstrates structured classroom implementation of natural object media, including seeds and twigs, within iterative action cycles to support early numeracy development. Implications The findings provide practical guidance for early childhood educators to utilize environmental resources as concrete learning media to support number symbol recognition and strengthen contextual numeracy learning in early childhood education settings. Highlights: Learning mastery increased from 0% at baseline to 80% after iterative classroom cycles. Children demonstrated progressive gains in counting, symbol identification, and quantity matching. Concrete environmental materials supported more engaging and contextual learning processes. Keywords: Natural Object Media, Number Symbol Recognition, Early Childhood Education, Classroom Action Research, Early Numeracy.